Loss of phosphatase and tensin homolog (PTEN) in myeloid cells controls inflammatory bone destruction by regulating the osteoclastogenic potential of myeloid cells. Issue 1 (27th September 2013) - Blüml, Stephan; Friedrich, Martin; Lohmeyer, Tobias; Sahin, Emine; Saferding, Victoria; Brunner, Julia; Puchner, Antonia; Mandl, Peter; Niederreiter, Birgit; Smolen, Josef S; Schabbauer, Gernot; Redlich, Kurt
Abstract : Objective: Local bone destruction in rheumatic diseases, which often leads to disability and severely reduced quality of life, is almost exclusively mediated by osteoclasts. Therefore, it is important to understand pathways regulating the generation of osteoclasts. Here, we analysed the impact of the Phosphoinositide-3-Kinase (PI3K)/Phosphatase and tensin homolog (PTEN) axis on osteoclast generation and bone biology under basal and inflammatory conditions. Methods: We analysed osteoclastogenesis of wildtype (wt) and PTEN −/− cells in vitro and in vivo, pit resorption and qPCR of osteoclasts in vitro. Mice with a myeloid cell-specific deletion of PTEN and wt littermate mice were investigated by bone histomorphometry and clinical and histological assessment in the human tumour necrosis factor (TNF)-transgenic (hTNFtg) arthritis model. Results: We show that myeloid-specific PTEN −/− mice display increased osteoclastogenesis in vitro and in vivo compared to wt mice. Loss of PTEN did not affect the generation or survival of osteoclast precursor cells. However, PTEN deficiency greatly enhanced receptor activator of nuclear factor κ-B ligand (RANKL)-induced expression of the master transcription factor of osteoclastogenesis, nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1), resulting in markedly increased terminal differentiation of osteoclasts in vitro. We also observed increased osteoclastogenesis under inflammatory conditions in the hTNFtg mouse model of arthritis, where hTNFtg/myeloid-specific PTEN −/− mice displayed enhanced local bone destruction as well as osteoclast formation in the inflamed joints. The extent of synovial inflammation, however, as well as recruitment of osteoclast precursor cells was not different between wt and myeloid-specific PTEN −/− mice. Conclusions: These data demonstrate that loss of PTEN and, therefore, sustained PI3-Kinase signalling in myeloid cells especially, elevates the osteoclastogenic potential of myeloid cells, leading to enhanced inflammatory local bone destruction. Therefore, although our study allows no direct translational conclusion since we used a conditional knockout approach, the therapeutic targeting of the PI3-Kinase pathway may be of benefit in preventing structural joint damage.